Harmonise syariah compliance regulations for sustainability, economic certainty - Omoola, Sodiq; Busari, Saheed Abdullahi (2022)
Experts discuss convergence and harmonisation of lasrm and regula- fions by high lighting the differences between and among two or more legal systems, such as common law, civil law and syariah law. Therefore, the common narrative among comparative law experts is to tell the different legal systems to live with one another without any one of them crossing their limits or jurisdiction. This narrative has been welt practised in Malaysia to a higher degree in business, governance, judiciary and other day-to-day affairs. Can harmonisation be discussed from within a particular legal system? This question seems unpopular..